Anti-Inflammatory and Antimicrobial Actions of Vitamin D in Combating TB/HIV. (1st July 2014) - Coussens, Anna K.; Martineau, Adrian R.; Wilkinson, Robert J.
Abstract : Tuberculosis (TB) disease activation is now believed to arise due to a lack of inflammatory homeostatic control at either end of the spectrum of inflammation: either due to immunosuppression (decreased antimicrobial activity) or due to immune activation (excess/aberrant inflammation). Vitamin D metabolites can increase antimicrobial activity in innate immune cells, which, in the context of HIV-1 coinfection, have insufficient T cell-mediated help to combat Mycobacterium tuberculosis (MTB) infection. Moreover, maintaining vitamin D sufficiency prior to MTB infection enhances the innate antimicrobial response to T cell-mediated interferon- γ . Conversely, vitamin D can act to inhibit expression and secretion of a broad range of inflammatory mediators and matrix degrading enzymes driving immunopathology during active TB and antiretroviral- (ARV-) mediated immune reconstitution inflammatory syndrome (IRIS). Adjunct vitamin D therapy during treatment of active TB may therefore reduce lung pathology and TB morbidity, accelerate resolution of cavitation and thereby decrease the chance of transmission, improve lung function following therapy, prevent relapse, and prevent IRIS in those initiating ARVs. Future clinical trials of vitamin D for TB prevention and treatment must be designed to detect the most appropriate primary endpoint, which in some cases should be anti-inflammatory and not antimicrobial.